The Extracellular Matrix in Soft Tissue Sarcomas: Pathobiology and Cellular Signalling - Pankova, Valeriya; Thway, Khin; Jones, Robin L.; Huang, Paul H. (Frontiers in Cell and Developmental Biology, 2021)
Soft tissue sarcomas are rare cancers of mesenchymal origin or differentiation comprising over 70 different histological subtypes. Due to their mesenchymal differentiation, sarcomas are thought to produce and deposit large quantities of extracellular matrix (ECM) components. Interactions between ECM ligands and their corresponding adhesion receptors such as the integrins and the discoidin domain receptors play key roles in driving many fundamental oncogenic processes including uncontrolled proliferation, cellular invasion and altered metabolism. In this review, we focus on emerging studies that describe the key ECM components commonly found in soft tissue sarcomas and discuss preclinical and clinical evidence outlining the important role that these proteins and their cognate adhesion receptors play in sarcomagenesis. We conclude by providing a perspective on the need for more comprehensive in-depth analyses of both the ECM and adhesion receptor biology in multiple histological subtypes in order to identify new drug targets and prognostic biomarkers for this group of rare diseases of unmet need.